2017
DOI: 10.1038/modpathol.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition-related proteins ZEB1, β-catenin, and β-tubulin-III in idiopathic pulmonary fibrosis

Abstract: Epithelial to mesenchymal transition has been suggested as a relevant contributor to pulmonary fibrosis, but how and where this complex process is triggered in idiopathic pulmonary fibrosis is not fully understood. Beta-tubulin-III (Tubβ3), ZEB1, and β-catenin are partially under the negative control of miR-200, a family of micro-RNAs playing a major role in epithelial to mesenchymal transition, that are reduced in experimental lung fibrosis and idiopathic pulmonary fibrosis. We wonder whether in situ expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 52 publications
4
48
1
1
Order By: Relevance
“…Treatment options for patients are limited 35 and the underlying mechanisms for fibrosis are still debated 36 . EMT has been suggested to have a direct role in IPF, with studies showing co-localisation of epithelial and mesenchymal markers [37][38][39][40][41] , and laser capture micro-dissection isolated RNA from epithelial cells in IPF lungs confirmed expression of mesenchymal markers 42 . However, lineage tracing studies found the number of fibroblasts derived from epithelial cells to be small 43,44 , and these cells were not found to colocalise with α-SMA suggesting they did not transition to myofibroblasts 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for patients are limited 35 and the underlying mechanisms for fibrosis are still debated 36 . EMT has been suggested to have a direct role in IPF, with studies showing co-localisation of epithelial and mesenchymal markers [37][38][39][40][41] , and laser capture micro-dissection isolated RNA from epithelial cells in IPF lungs confirmed expression of mesenchymal markers 42 . However, lineage tracing studies found the number of fibroblasts derived from epithelial cells to be small 43,44 , and these cells were not found to colocalise with α-SMA suggesting they did not transition to myofibroblasts 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The two ZEB family members, ZEB1 and ZEB2, are transcriptional inhibitors that are involved in cell proliferation, migration, invasion, and apoptosis. Extensive studies have confirmed that ZEB1 is upregulated in the EMT and plays a key role in the development of tumors and fibrosis . It was reported that the Np63‐miR‐205 axis increased epithelial marker gene expression and decreased mesenchymal marker gene expression in oral squamous cell carcinoma by downregulating ZEB1 and ZEB2 .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…Extensive studies have confirmed that ZEB1 is upregulated in the EMT and plays a key role in the development of tumors and fibrosis. 99,100 It was reported that the Np63-miR-205 axis increased epithelial marker gene expression and decreased mesenchymal marker gene expression in oral squamous cell carcinoma by downregulating ZEB1 and ZEB2. 101 Moreover, the heterogeneous expression of ZEB1 induced by EMT played an important role in metastasis through the regulation of miR-200c.…”
Section: Zeb Transcription Factorsmentioning
confidence: 99%
“…One important role for β ‐catenin is induction of a morphogenic change in epithelial cells . During this process, epithelial cells cease to express E‐cadherin, Zonula occludens 1 (ZO1) protein, and cytokeratin and begin to synthesize vimentin, alpha smooth muscle actin (ACTA2), and fibroblast‐specific protein 1 (FSP1) . β ‐catenin expression is disturbed in many types of cancer.…”
Section: Introductionmentioning
confidence: 99%